Clinical effect of external ventricular drainage under intracranial pressure monitoring in the treatment of aneurysmal subarachnoid hemorrhage patients and investigation of the mechanism of miR-146a-5p/STC1 axis in inhibiting early brain injury in aneurys: miR-146a-5p/STC1 axis in inhibiting early brain injury - Wang, Changqiang; Sun, Jingjing; Liu, Junling (Cellular and Molecular Biology, 2024)
Aneurismal subarachnoid hemorrhage (aSAH) is a common disease in the neural system, with high death rate. Our study aimed to explore the clinical effect of external ventricular drainage under intracranial pressure monitoring in the treatment of patients with aSAH and investigate the role along with mechanism of miR-146a-5p in aSAH. Ninety-six aSAH patients were allocated into control group (CG) and study group (SG). The CG was released by lumbar puncture. The SG underwent external ventricular drainage based on intracranial pressure monitoring. The prognosis, daily living ability, neurological function, S100β and NSE (neuron-specific enolase) levels and incidence of complications were monitored. Besides, a rat model of SAH was built to assess the neurobehavioral function, blood-brain barrier permeability, brain water content, neuronal apoptosis as well as inflammation. SAH cell model stimulated by oxyhemoglobin, and cell apoptosis as well as inflammation were measured. Luciferase reporter assay was implemented to explore the interaction between miR-146a-5p and STC1. Results showed higher GOS and BI scores but lower NIHSS scores, S100β and NSE levels and complication rates in SG compared with CG. Additionally, miR-146a-5p presented down-regulation in brain tissues of SAH rat model, and overexpressed miR-146a-5p reduced brain injury along with neuroinflammation in SAH rat model. Oxyhemoglobin-induced nerve cell apoptosis along with inflammation after SAH, and overexpressed miR-146a-5p repressed oxyhemoglobin-induced nerve cell apoptosis along with inflammation. STC1 is the target mRNA of miR-146a-5p, and overexpressed miR-146a-5p represses oxyhemoglobin-induced nerve cell apoptosis along with inflammation via regulating STC1 expression. In conclusion, external ventricular drainage under intracranial pressure monitoring could promote prognosis, promote daily living ability, improve neurological function, reduce S100β protein and NSE levels, and reduce the incidence of complications in patients with aSAH. Meanwhile, miR-146a-5p inhibited early brain injury and neuroinflammation in aSAH via regulating STC1 expression.